2012
DOI: 10.1177/0021998312462618
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical analysis and free vibration behavior in chemical modifications of coconut sheath/nano-clay reinforced hybrid polyester composite

Abstract: Naturally woven coconut sheath, a new natural fiber available in the form of woven mat is used as fiber reinforcement in polyester matrix. The hybridization effect of montmorillonite (MMT) on naturally woven coconut sheath/polyester composite has been investigated experimentally for free vibration characteristics using impulse excitation technique (IET). In the present study, naturally woven coconut sheath/clay-reinforced hybrid polyester composites were fabricated using a compression molding machine. The effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(44 citation statements)
references
References 40 publications
1
41
0
2
Order By: Relevance
“…6 and 7, respectively. Figure 6 shows the decrease in the storage modulus with increasing temperature because of the dilute nature of the polymer at all of the pH conditions (Rajini et al 2013). It was clearly shown that the highest storage modulus (E') was obtained for F5pH10 at room temperature.…”
Section: Dynamic Mechanical Thermal Analysis (Dmta)mentioning
confidence: 98%
“…6 and 7, respectively. Figure 6 shows the decrease in the storage modulus with increasing temperature because of the dilute nature of the polymer at all of the pH conditions (Rajini et al 2013). It was clearly shown that the highest storage modulus (E') was obtained for F5pH10 at room temperature.…”
Section: Dynamic Mechanical Thermal Analysis (Dmta)mentioning
confidence: 98%
“…The rectangular composite specimens of size 50 Â 10 Â 3 mm 3 were used [25]. The test was conducted by using a three-point bending mode.…”
Section: Measurements Of Dma and Tgamentioning
confidence: 99%
“…However, for the specimen in the form thin rectangular section can be analyzed more convincingly using impact hammer technique as per the previous research outcomes [29,35,36]. Accordingly, from the literature the standard specimen of size 200 Â 20 Â 3 mm composite plate was selected for the free vibration analysis.…”
Section: Vibration and Chemical Resistant Testmentioning
confidence: 99%
“…However, among various particle size the decreasing particle size can have better strength compared to larger particle size for a fixed wt% of filler content. It is a well known fact that the decrease in particle size can increase the surface to contact area of the filler in bulk matrix [36]. It also ensures the uniform dispersion of redmud in polyester matrix from the increasing value of tensile strength.…”
Section: Tensile Strengthmentioning
confidence: 99%
See 1 more Smart Citation